The effectiveness of online recruitment / Najattul Husna Mahmud - Mahmud, Najattul Husna (2013)
This purposed of this study is to understand the effectiveness usmg online recruitment system at Pusat Kerjaya Amanjaya, UTC Kinta, Perak. The respondents were employees and employers in government sector. This study consists of demographic questions and ten questions that are related regarding with the usage of online recruitment. Respondents agreed that professiona1 sites· or career bank is mostly used to attract future employees. Majority of them also stated that social networking sites are better in attracting future employees compared to professional sites or career bank and third party staffing. The main reason for using e-recruitment is the accessibility broader pool. Most of the respondents prefer job matching system being used to screen for future employees. They also agree that e-recruitment system should replace the traditional approach and the system evolved to be more effective way to develop competitive human capital by overall.